Challenges of electricity market liberalization in the Baltic countries - Anna-Greta Tsahkna; Diana Eerma (OrdnungsPolitisches Portal (OPO), 2010)
In the article there are analyzed the electricity market opening issues in the European Union and especially in the Baltic countries. The aim of the article is to find out and specify the main challenges for Baltic countries in electricity market liberalization process. The Baltic countries are going to face many challenges to secure their energy supply and cooperate regionally. For completion of the research task there are analyzed experiences from Scandinavian countries electricity market liberalization.
Keywords: 330; Economics of Regulation; Government Policy and Regulation; Regulated Industries; Electricity Market; Elektrizitätswirtschaft; Deregulierung; Nordosteuropa